F-HMIPv6 환경에서의 비용 효율적인 MAP 선택 기법 - 노명화(Myoung Hwa Roh); 정충교(Choong Kyo Jeong) (韓國컴퓨터情報學會誌, 2006)
In this paper, we propose a new automatic fingerprint identification system that identifies individuals in large databases. The algorithm consists of three steps: preprocessing, classification, and matching, in the classification, we present a new classification technique based on the statistical approach for directional image distribution. In matching, we also describe improved minutiae candidate pair extraction algorithm that is faster and more accurate than existing algorithm. In matching stage, we extract fingerprint minutiaes from its thinned image for accuracy, and introduce matching process using minutiae linking information. Introduction of linking information into the minutiae matching process is a simple but accurate way, which solves the problem of reference minutiae pair selection in comparison stage of two fingerprints quickly. This algorithm is invariant to translation and rotation of fingerprint. The proposed system was tested on 1000 fingerprint images from the semiconductor chip style scanner. Experimental results reveal false acceptance rate is decreased and genuine acceptance rate is increased than existing method. F-HMIPv6(Fast-Hierarchical Mobile IP version 6) 네트워크에서는 단말의 이동을 관리하기 위해 MAP(Mobility Anchor Point)를 사용한다. 현재는 매크로 핸드오프 발생 시 단말로부터 가장 멀리 떨어져있는 MAP을 선택하는 기법을 사용하고 있다. 그러나 이 경우 하나의 큰 MAP으로 전체 부하가 몰리는 문제와 이동 단말과 MAP간의 긴 거리로 인해 통신 비용이 증가하는 문제가 있다. 이 연구에서는 단말의 이동속도와 패킷 전송률을 고려하여 통신 비용을 최소화 하는 비용 효율적인 MAP을 선택 기법을 제안한다. 이를 위해 통신 비용을 바인딩 업데이트 비용과 데이터 패킷 전달 비용으로 구분하고 이 통신 비용을 최소화하는 MAP의 크기를 수식으로 표현한다.